Specific Features of the Subjective Picture of Life as Predictors of Readiness for Innovations of Future Law Enforcement Officers (Law and Safety, 2019)
The objective of the research was to study the peculiarities of the subjective picture of life as personal predictors of the readiness of future law enforcement officers for innovations.The diagnosis of readiness for innovations was carried out using the questionnaire “Personal readiness for changes”. To diagnose the peculiarities of the subjective picture of life (psycho-biological indicators), the author has used semantic time differential, the Zimbardo Time Perspective Inventory (ZTPI), and the questionnaire “Estimation of five-year intervals”. In the process of statistical processing the author has carried out a multiple regression analysis (by the straight-line stepwise method).As a result of the research, seven regression equations containing indicators of the features of the subjective picture of life, indicating the significance of their influence on components of innovation readiness, have been constructed.It has been proved that the time perspective “Future” is the most influential predictor for the development of readiness for innovations of future law enforcement officers. Strong predictors with reverse effect are the time perspective “Fatalistic present” and the indicator “Feasibility”.It has been demonstrated that moderate positive influence on the development of the innovative readiness of future law enforcement officers makes unconscious positive assessments of the present and future and realized perceptions of the richness of life by significant events and the time perspective of “Positive past”. A moderate negative impact on the development of readiness for changes is done by the time perspective “Negative past”.It has been revealed that the time perspective “Goddess present” enhances the development of passion and hinders the development of courage in the structure of innovation readiness.The results of regression analysis prove that the peculiarities of the subjective picture of life, which include the estimation of the unconscious attitude to the present, past and future, time perspectives and perceived assessments of the past, present and future events saturation are significant predictors of the development of innovation readiness of future law enforcement officers.
Keywords: readiness for innovations; future law enforcement officers; subjective picture of life cycle; time perspectives; psychological time